Studi Pengaruh RTH Alun-Alun Kota Terhadap Kehidupan Sosial Masyarakat Sebagai Kawasan Ruang Publik Di Kota Pangkajene Kabupaten Pangkep - Glorya Day, Elsa; Surya, Batara; Taking, Muh Idris (Journal of Urban Planning Studies, 2024)
The aims of this research is to find out the perception and influence of the Citra Mas Square Green Open Space on the social life of the people in Pangkajene City and to find out whether the square Green Green Space has a big impact on every aspect of people's life in Pangkajene City such as the use of sports infrastructure and trade, garden, seating and others. This research is quantitative research with data collection techniques: interviews, questionnaires, surveys, observations and documentation with sampling techniques using probability sampling or random samples using the Simple Random Sampling approach. The data obtained was then analyzed using descriptive analysis and Chi-Square analysis. The main conclusion from this study is that Citra Mas Square Green Open Space has a good influence on society where people use the square green open space as a location to gather, exercise, play and some people even use the location as a trading location. However, some people also believe that in the Citra Mas Square RTH there are still a lack of children's play facilities, there are insufficient rubbish bin facilities and there are no public toilet facilities available for people who visit the Citra Mas Square Green Open Space. So in the future there is a need to improve and provide facilities that are still lacking in the Citra Mas Square Green Open Space, and the role of the Government is really needed in improving the quality and facilities in the Citra Mas Square Green Open Space.